Tourist spaces and tourism policy in Spain and Portugal - Almeida-García, Fernando; Cortés-Macías, Rafael; Balbuena-Vázquez, Antonia (My University, 2015)
This study analyses the relationship between the development of the tourism policy of Spain and Portugal and their effects on regional imbalances. Despite the proximity of the two countries and their specialisation in tourism, there are few comparative studies on tourism of the two Iberian countries. The study focuses on the two major phases of tourism policy: the period of mass tourism and post-Fordist stage. In the conclusions we refer the debate on the existence of a model of development based on tourism to the Latin countries of Southern Europe and we note the export process of the Spanish low-cost tourism model to other countries.
Advances in Cultura, Tourism and Hospitality Research;10, 235-249
Keywords: Política turística - España; Política turística - Portugal; Spain; Portugal; Tourism; Policy tourism; Tourism spaces